4 - The Use of Social Science Research by Environmental NGOs in Africa: Evidence from Morocco - El Morchid, Brahim; Allah, Hind Hourmat (Africa Development, 2021)
The literature on the use of research is both rich and varied. Yet, little is known about the use of available social research by environmental NGOs in the African context. This paper aims at contributing to the debate on this issue from the perspective of Moroccan civil society. In order to achieve this objective, we have analysed the results of a survey conducted among a sample of Moroccan NGOs working in environmental protection. Overall, it seems that a relatively large proportion of surveyed environmental NGOs receive and understand social research findings, but the process remains incomplete, as the use of these findings tends to diminish during the adoption stage and especially during the decision-influencing stage. Moreover, this conclusion must be regarded cautiously, given the confusion that arises from the lack of distinction between research and consulting activities. Finally, PLS regression reveals that the use of social science research by Moroccan environmental NGOs is influenced by three main factors: research adaptation effort, relational proximity between researchers and users, and the NGO director’s employment status.